1999
DOI: 10.1093/oxfordjournals.aje.a009908
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of People Reporting Sensitivities to Chemicals in a Population based Survey

Abstract: To describe the prevalence and correlates of reports about sensitivities to chemicals, questions about chemical sensitivities were added to the 1995 California Behavior Risk Factor Survey (BRFS). The survey was administered by telephone to 4,046 subjects. Of all respondents, 253 (6.3%) reported doctor-diagnosed "environmental illness" or "multiple chemical sensitivity" (MCS) and 643 (15.9%) reported being "allergic or unusually sensitive to everyday chemicals." Sensitivity to more than one type of chemical was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
170
5
6

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(196 citation statements)
references
References 21 publications
15
170
5
6
Order By: Relevance
“…The survey, administered in 1998, took samples from different regions of the state and included more than 4,000 respondents. Kreutzer et al (1999) found that 15.9% of respondents reported unusual sensitivity to common chemicals, which tended to confirm the original NAS estimate (NAS 1981). The CDHS study (Kreutzer et al 1999) also included data on sex, educational level, marital status, and racial/ethnic linkage with MCS.…”
Section: Mcs Prevalencementioning
confidence: 51%
See 3 more Smart Citations
“…The survey, administered in 1998, took samples from different regions of the state and included more than 4,000 respondents. Kreutzer et al (1999) found that 15.9% of respondents reported unusual sensitivity to common chemicals, which tended to confirm the original NAS estimate (NAS 1981). The CDHS study (Kreutzer et al 1999) also included data on sex, educational level, marital status, and racial/ethnic linkage with MCS.…”
Section: Mcs Prevalencementioning
confidence: 51%
“…Kreutzer et al (1999) found that 15.9% of respondents reported unusual sensitivity to common chemicals, which tended to confirm the original NAS estimate (NAS 1981). The CDHS study (Kreutzer et al 1999) also included data on sex, educational level, marital status, and racial/ethnic linkage with MCS. Earlier anecdotal evidence had suggested that white women of higher educational status disproportionately reported MCS (Cullen 1992).…”
Section: Mcs Prevalencementioning
confidence: 51%
See 2 more Smart Citations
“…Furthermore there are no validated objective methods to measure or detect this condition. A number of population based studies have suggested that sensitivity to chemicals is a common problem with reported estimates ranging from 6-18% [20,21]. A number of studies designed to determine the prevalence of odour intolerance or self-reported illness from chemical odours in the general healthy population have reported prevalence rates of 33% and 66% respectively with predominance amongst female study participants [,22,23].…”
Section: How Common Is Airway Sensory Hyperreactivity (Shr)?mentioning
confidence: 99%